Trends and Clinical Implications of Pediatric Pulmonary Function After Hematopoietic Stem Cell Transplantation: A Systematic Review - Xiaowei Zhao; Yuqi Zhao; Guoyu Ding; Xue Li; Xiaoyue Zhang; Yanli Leng; Hongmei Wang (Health Science Reports)
ABSTRACT Background and Aims Hematopoietic stem cell transplantation (HSCT) is a key therapeutic approach for pediatric patients with hematologic and non‐hematologic disorders. However, post‐transplant pulmonary complications remain a significant cause of morbidity and mortality. Pulmonary Function Tests (PFTs) are essential for the early detection of pulmonary dysfunction, yet their application in pediatric HSCT recipients has yielded inconsistent results. This review aims to assess the variations in pulmonary function post‐HSCT and explore their clinical implications for pediatric patients. Methods A systematic review was conducted by analyzing studies published between 2000 and 2024, sourced from PubMed, Web of Science, CNKI, and Wan Fang databases. The review included cohort studies, randomized controlled trials, and case‐control studies that assessed pulmonary function using standardized PFTs. Results Pulmonary dysfunction, particularly obstructive and restrictive ventilatory disorders, is common in pediatric HSCT recipients. Significant changes in PFT parameters, such as FEV1/FVC ratio and FEF25‐75%, were observed. However, trends in post‐transplant pulmonary function vary due to factors such as pre‐transplant lung conditions, patient age, and treatment protocols. Innovative diagnostic methods, such as parametric response mapping (PRM) and multiple breath washout (MBW), show promise in enhancing early detection and management of pulmonary complications. Conclusion Monitoring pulmonary function is critical for the early identification of complications in pediatric HSCT recipients. Although standardized clinical guidelines are available, variability in PFT trends underscores the need for more refined diagnostic tools. Advanced diagnostic methods, like PRM and MBW, may improve early detection and help optimize the management of pulmonary dysfunction, ultimately improving long‐term outcomes for pediatric patients.